2017
DOI: 10.1186/s12889-017-4605-0
|View full text |Cite|
|
Sign up to set email alerts
|

Population-based prevalence survey of follicular trachoma and trachomatous trichiasis in the Casamance region of Senegal

Abstract: BackgroundTrachoma, caused by ocular infection with Chlamydia trachomatis, is the leading infectious cause of blindness worldwide. We conducted the first population-based trachoma prevalence survey in the Casamance region of Senegal to enable the Senegalese National Eye Care Programme (NECP) to plan its trachoma control activities. The World Health Organization (WHO) guidelines state that any individual with trachomatous trichiasis (TT) should be offered surgery, but that surgery should be prioritised where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
4
9
1
Order By: Relevance
“…Among the factors investigated, it was observed that girls had greater chances of contracting trachoma in Pernambuco and in the mesoregion of Zona da Mata. This association has also been reported in population-based surveys in Senegal [24], Ethiopia [25], Gambia, and Tanzania [13]. This is probably because girls more frequently help in tending to younger siblings and because affective behavior is closer among girls [13,25].…”
Section: Discussionsupporting
confidence: 71%
“…Among the factors investigated, it was observed that girls had greater chances of contracting trachoma in Pernambuco and in the mesoregion of Zona da Mata. This association has also been reported in population-based surveys in Senegal [24], Ethiopia [25], Gambia, and Tanzania [13]. This is probably because girls more frequently help in tending to younger siblings and because affective behavior is closer among girls [13,25].…”
Section: Discussionsupporting
confidence: 71%
“…However, it was higher than other related studies conducted in different parts of Ethiopia: Baso Liben District (24.1%) [ 14 ], Oromia Region (23.4%) [ 13 ], Amhara (21.6%) [ 5 ], Somali (22.6%), SNNPR (33.2%), Tigray (26.5%), and Gambella (19.1%) [ 7 ], and Dera Woreda (15.6%) [ 15 ], Dembia District (18%) [ 3 ], South Wollo (26.4%) [ 16 ], and Harari Regional State (1.3%) [ 17 ]. It was also higher than related studies from Senegal (2.5%) [ 8 ], Nigeria (0.04–19%) [ 18 ], Kenya (18.7%) [ 2 ], and Burkina Faso (9.5%) [ 19 ]. The difference might be due to the difference in sample size and study population, and the disparities in the socioeconomic status of the respondents.…”
Section: Discussionmentioning
confidence: 53%
“…Considerable regional variations are observed in the occurrence of active trachoma; the highest prevalence is in Amhara (62.6%), Oromia (41.3%), and Southern Nations, Nationalities, and People's Region (SNNPR) (33.2%), Tigray (26.5%), Somali (22.6%), and Gambella (19.1%). The rural prevalence of active trachoma is almost fourfold compared to the urban prevalence (42.5% rural vs. 10.7% urban) [ 2 , 5 , 8 ]. The national prevalence of trachomatous trichiasis (TT) is 3.1% with the highest prevalence in Amhara Regional State (5.2%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Between 2004 and 2013, district-level baseline surveys were completed in 37 districts (Table 1), using WHO-recommended methods and sampling 30 clusters per district. 12,13 These surveys were conducted incrementally as funds became available, with priority given to zones that were expected to be at greater risk of trachoma based on the findings of the region-level prevalence surveys.…”
Section: Introductionmentioning
confidence: 99%